Pengelolaan Konten Website Pemerintah Kota Yogyakarta sebagai Media Pelayanan Publik - , Galih Akbar Prabowo ([Yogyakarta] : Universitas Gadjah Mada, 2013)
As one of governmental institutions that had a commitment in developing a governmental website as public service facility, the Government of Yogyakarta City was demanded to be able to manage their website content as an effort to implement a quality public service. This research was aimed to identify and evaluate the Government of Yogyakarta Cityâs efforts in managing its website content. Overall, the Government of Yogyakarta City website content management had been conducted well. However, from a public service perspective, the service which delivered by the Government of Yogyakarta City had some disadvantages. Even itâs not maximum yet, transparency, responsiveness, effectiveness, efficiency, and also accountability aspects had emerged in the website content management of the Government of Yogyakarta City as public service media.